Influence of Different Additives at Various Contents on the Properties of Pottery Clay Body - LIMPAIBOON, Kongdej; NUALANONG, Amnuay (Walailak Journal of Science and Technology (WJST), 2011)
The preparation of clay body is a highly important step during the production of local decorative pottery, especially the local unglazed low-fired terracotta. In this study, sand (size < 178 mm) and Bulrush pulp were employed as an additive blended with clay (size < 125 mm) in the preparation of clay body. Various sand contents (2 - 18 wt%) and pulp contents (1 - 14 wt%) were tested. The properties of each clay body were evaluated in terms of shrinkage, water absorption and modulus of rupture. The results obtained showed that higher sand or pulp content gave higher water absorption and lower shrinkage of clay body. The dried MOR value of pulp-clay body was much higher than that of sand-clay body at the same content. The maximum fired MOR value of sand-clay body (84.51 kgf/cm2) at sand content of 2 wt% was a little higher than that of pulp-clay body (80.44 kgf/cm2) at pulp content of 4 wt%. However, at a sand content ranging between 2 and 14 % or a pulp content ranging between 1 and 5 %, the fired MOR values of clay bodies were enhanced above that of local pottery clay body (60.14 kgf/cm2). From these results the pulp could adequately be used as an additive as well. Finally, a suitable sand or pulp content for producing smooth clay bodies was between 2 and 14 wt% or between 1 and 4 wt%, respectively, due to clay bodies obtained having more smooth texture and higher strength than local pottery clay body.